Determination of the Acidity of MCM-41 with Different Si/Al Ratios by the Temperature Programmed Desorption of Pyridine - Marcelo J.B. Souza; Stevie H. Lima; Antonio S. Araujo; Anne M. Garrido Pedrosa; Ana C.S.L.S. Coutinho (Adsorption Science & Technology)
Mesoporous catalysts of MCM-41 type with different Si/Al ratios were synthesized by the hydrothermal method and characterized by X-ray diffraction, nitrogen adsorption and thermogravimetric analysis. Their acidic properties were determined via the temperature programmed desorption of pyridine. Vyazovkin kinetic models were used to correlate the total acidity as a function of the Si/Al ratio with the apparent activation energy for pyridine desorption. The results obtained indicated that the catalysts possessed weak and medium acidic sites. An increase in the Si/Al ratio led to an increase in the activation energy for pyridine desorption.